ANALISIS HUBUNGAN FAKTOR-FAKTOR SOSIAL EKONOMI PETANI DENGAN PRODUKSI JAGUNG DI DESA WARINTA KECAMATAN PASARWAJO KABUPATEN BUTON - Mustari, La Ode Muhammad (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2017)
This study aims to determine the relationship of socio-economic factors of farmers with corn production in Warinta Village, Pasarwajo Sub-district, Buton Regency. This research was conducted in Warinta Village, Pasarwajo Sub-district, Buton Regency for one month from June to July 2012. The population of this study was corn farmers in Warinta Village. The study sample took 35 corn farmers. Data were collected through interviews using a list of questions and analyzed using descriptive analysis. From the results of the study, it was concluded that there was a relationship between farmer's socioeconomic factors (level of education, farming experience, number of family dependents and land area) with corn production in Warinta Village, Pasarwajo District, Buton Regency.   Keywords: Corn production, Farmers' socioeconomic factors